Validation of the 12‐item World Health Organization Disability Assessment Schedule 2.0 in individuals with schizophrenia, depression, anxiety, and diabetes in Singapore - Abdin, Edimansyah; Seet, Vanessa; Jeyagurunathan, Anitha; Tan, Sing Chik; Mok, Yee Ming; Verma, Swapna; Lee, Eng Sing; Subramaniam, Mythily (PloS one, 2023)
There is limited evidence on the reliability and validity of the 12-item World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) in an Asian patient population with mental and physical disorders. The current study aimed to examine the psychometric properties of the WHODAS 2.0 among patients with schizophrenia, depression, anxiety, and diabetes. A total of 1076 patients (M = 40.9 years, SD = 14.7) were recruited from the outpatient clinics of a tertiary psychiatric hospital and a primary care clinic. Internal consistency and test-retest reliability, structural validity, convergent validity, agreement, and floor and ceiling effects were examined. Our confirmatory factor analysis (CFA) showed that the 1-factor model fits our data. Multigroup CFA demonstrated metric and scalar invariance, indicating the scores can be compared across the four conditions. The WHODAS 2.0 scale had excellent reliability in the overall sample and good to excellent reliability across conditions. The test-retest reliability and agreement between self-administered and interviewer-administered modes were good. The WHODAS 2.0 scores had moderate to strong correlations with the Social and Occupational Functioning Scale and the Sheehan Disability Scale scores in the overall sample and across four conditions.